The Effect of Legal Protection Innovation and Marketing Education on the Performance of Banjarbaru City MSMEs In The Era Of Society 5.0 - Wahyudi, Wahyudi; Widyanto, Rinto; Effendi, Ibrahim Rully; Rahayu, Aesty; Muslim, Abdul Aziz; Aji, Ifan Anom Bintoro (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2024)
This study aims to analyze the influence of legal protection innovation and marketing education on the performance of Micro, Small and Medium Enterprises (MSMEs) in Banjarbaru City in the context of the Society 5.0 era. The Society 5.0 era emphasizes the important role of digital technology in various sectors, including MSMEs. MSMEs play a significant role in the Indonesian economy, but face various challenges, such as increasingly tight competition and changes in market patterns towards digital. This study uses a quantitative approach with a sample of 26 MSMEs from a total population of 10,869 registered in Banjarbaru City. Data were collected through questionnaires and processed using non-parametric statistical analysis, such as Spearman Rank Correlation and Kruskal-Wallis, because the data were not normally distributed. The results of the study indicate that legal protection innovation does not have a significant effect on MSME performance, with a correlation coefficient of -0.026 and a significance value of 0.901. In contrast, marketing education has a significant positive effect on MSME performance, with a correlation coefficient of 0.591 and a significance value of 0.001. This confirms that MSMEs who receive better marketing education tend to have higher performance, especially in terms of sales growth, customers, and profits. This study also found significant differences in MSME performance based on age, with older age groups showing higher levels of education and better MSME performance. In conclusion, although innovations in legal protection have not shown a significant impact, marketing education has been shown to play an important role in improving MSME performance in the digital era. This study recommends improving marketing training and education programs for MSMEs to strengthen their competitiveness in an increasingly modern and digital market.